(3ehdO GdHTjQ GdfPjQ GdSQGL GdefjQ efXheIs - (3eMeO CHh GdhaGAs
(3ChdgG (B:s
(3HSe QH GdYQT NdGb GdCfGe (B*** (3fHJOj aj GdPcQ ef bHd GdfXGe , cd PcQ bHdg PcQ GdEdg (B*** (3Ef JdGg PGcQ jHdZ efGg , Ef PcQ Gddg eUHGM GdbdhH (B*** (3jefM GdCdHGH eaJGM GdZjhHs
(3BNQgG (B:s
(3jG Edgj dG JRd YfG GdfYe (B*** (3hCfdfG efc CfhGY GdcQe , jG Edgj Mhd GdMGd Edi (B*** (3CMSf GdMGd hgHfG GdCedG , hJMjGJ hCaVd GdSdGe (B*** (3dEeGe GdCfHGA hgh NJGes
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJGQjNs